PENDIDIKAN MULTIKULTURAL DI INDONESIA: ARAH DAN MANFAATNYA - Ola Rongan Wilhelmus (Bahasa Indonesia, 2018)
Abstract Socially and culturally, Indonesia is one of the very compounds in the world. This fact can be seen from socio-cultural and geographical life situation a very pluralist Indonesia. Aloofness and don't value one against the other in their life together are generally rooted in the social and cultural structure that does not reflect the equality tribe, race, religion, culture and between groups. Pressure and oppression perpetrated by groups of the society and culture of the majority against the minority in the field of social life, culture, economy and politics will bear the tension as well as social and cultural conflicts that are not endless and very detrimental to life together. Therefore need to be encouraged and carried out concrete efforts to develop the study of the diversity of social groups, cultures and ethnicities in order to draw up an educational curriculum of multiculturalism for the elementary school students to students in College. Education of multiculturalism can erode the attitude in addition to expected life of hypocrisy, egoistic and individualistic, but also helps a person to develop the process of identification and recognition of the reality of plurality. Multicultural education not only could produce human beings who have job skills but also the ability to understand, appreciate, and implement a live up to the values of democracy, humanity and plurality.